The importance of empowerment and empowering personnels - Kocabaş, Ibrahim; Karaköse, Turgut (My University, 2006)
Organizations are always obliged to devoloping for his own benefit. One of the most important conditions of success is to reach the quality at product and service. Thanks to that the business is able to stay afloat. For this reason it's important personnel must be trained as connected with their jobs. At first managements must trust their personnels. Personnels are become the owner of skills concerned with their jobs. For this reason, personnel is must be taken courage and is supported by managers in connecttion with to product new ideas.
Yetki?lendi?rmeni?n önemi?ve çalişanlarin yetki?lendi?ri?lme?i
Keywords: Communication; Confidence; Empowerment; Responsibility